IRX3 plays an important role in the pathogenesis of metabolic-associated fatty liver disease by regulating hepatic lipid metabolism - Ma, Yongqiang; Chen, Guangshun; Yi, Junfang; Li, Qiang; Tan, Zhi; Fan, Wenling; Luo, Xiaohua; He, Zhiyong; Si, Zhongzhou; Li, Jiequn (Frontiers in Endocrinology, 2022)
Metabolic-associated fatty liver disease (MAFLD) affects approximately a quarter of the global population. Identification of the key genes and pathways involved in hepatic lipid metabolism is of the utmost importance for the diagnosis, treatment, and prevention of MAFLD. In this study, differentially expressed genes were identified through whole-genome transcriptional analysis of liver tissue from MAFLD patients and healthy controls, and a series of lipid metabolism-related molecules and pathways were obtained through pathway analysis. Subsequently, we focused on Iroquois homeobox protein 3 (IRX3), one of 13 transcription factors that were screened from the 331 differentially expressed genes. The transcription factor IRX3 was significantly decreased in the liver tissue of patients with MAFLD when compared with healthy controls. Pearson’s correlation analysis showed that the expression levels of IRX3 in liver tissue were negatively correlated with serum total cholesterol, triglycerides, low-density lipoprotein cholesterol, and uric acid levels. The overexpression and interference of IRX3 induced the increased and decreased lipid droplet accumulation in vitro, respectively. Moreover, interference of IRX3 expression increased mitochondrial fragmentation and reduced the activity of the mitochondrial respiratory chain complex IV In summary, the study demonstrated that IRX3 regulated hepatic lipid metabolism of MAFLD, and also revealed the effect of IRX3 on mitochondria might be an important mechanism by which IRX3 regulated hepatic lipid metabolism of MAFLD.